Membangun Karakter Melalui Pendidikan: Evaluasi terhadap Program Pendidikan Karakter di Sekolah Dasar - Suryati, Dewi; Arifianto, Yonatan Alex; Triposa, Reni (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
Education has an important role in shaping individual knowledge and character to face the times. Education not only affects knowledge, but also affects a person's behavior both as an individual and in social life. Every action people take in a social environment can affect the quality of their lives, and positive deeds play an important role in creating an atmosphere of peace. Therefore, it is important to conduct an assessment of one's character to find out the mistakes made and provide direction for improvement. This study aims to evaluate the importance of character education in shaping positive attitudes and behaviors, and to see the extent to which good character can be a mirror and blessing for oneself and others. The method used in this study is a qualitative approach with interviews, observations and document analysis related to character education in the school environment. The results showed that good character education can help individuals to be more careful in their actions and interactions, and have a positive impact on their social life.